Kinetic study and modelling of fe (iii) ions removal by duck egg shells - Ang, Li Wei (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This project was conducted to study on the adsorption of Fe (III) ions by using duck egg shells which acts as adsorbents. The comparison between natural duck egg shells and calcinated duck egg shells also had been studied in this project. The morphology structure of these two duck egg shells were investigated using FESEM. Besides that, the effect of different parameters such as temperature, pH and dosage on Fe (III) ions removal also had been studied. The Langmuir and Freundlich isotherms were applied to determine its adsorption behaviour. Meanwhile, the pseudo-first order and pseudo-second order also were used to test its adsorption suitability. Waste water was collected to determine the adsorption capability on Fe (III) ions by using duck egg shells. From this project, it was found out that duck egg shell has the potential to become a good low cost adsorbent. The calcinated duck egg shell has greater adsorption capability than the natural duck egg shells.